Managing behavior in organizations - Greenberg, Jerald (Pearson, 2013)
This book provides a brief tour of the scientific and practical highlights of organizational behavior (OB). This text focuses on the essential concepts and practices that students need to know while offering instructors an array of material that can be tailored to their style of teaching.